(untitled) (Revista de Crítica Literaria Latinoamericana, 2016)
The publication of Garcilaso de la Vega’s Comentarios reales in 1609 contributed to an idealized image of the ancient Incas in Europe, an image that was very successful in eighteenth century France. For the Philosophers of the Lights, the Inca society established a model of enlightened despotism, by which the monarchs of their time could be inspired. Strengthened by its new international legitimacy, the idealized representation of the Incas returned triumphantly to Peru, where a movement known as “Inca Renaissance” was flourishing. Antonio Valdez used this image to give life to the characters of his play Ollantay (1782) in the Quechua language.